The Ngupati Tradition of the Buntet Pesantren Community in Social and Cultural Dimensions - Abbas, Faiz Musthofa (UIN SIber Syekh Nurjati Cirebon, 2025)
The Ngupati tradition is a unique cultural practice among Javanese society, particularly in Buntet Pesantren, Cirebon, West Java. Ngupati is performed during the fourth month of pregnancy, following the Neloni ceremony in the third month and preceding the Mitonan in the seventh month. This tradition involves Quranic recitations, prayers, and communal gatherings, reflecting gratitude for God's blessings and prayers for the unborn child's safety. This study explores the history, cultural significance, and social impact of the Ngupati tradition within the Buntet Pesantren community. Using a qualitative approach, data were collected through interviews, observations, and literature reviews. Findings reveal that Ngupati serves as a medium for preserving ancestral heritage, reinforcing social cohesion, and embodying religious devotion. The practice also highlights the integration of religious and cultural values in Javanese society. Additionally, Ngupati contributes to the community's social structure by fostering mutual respect and collective responsibility. As a symbol of cultural resilience, the Ngupati tradition continues to thrive amidst modernization, reflecting the adaptability of Javanese traditions in contemporary society. This research emphasizes the importance of understanding traditional ceremonies to appreciate their role in shaping and sustaining cultural identities.